Effects of combined special education treatment and occupational therapy on upper extremities motor skills in adult patients with hemiplegia - Savković, Nada Radomir (Vojnosanitetski pregled, 2017)
Background/Aim. Stroke is the most common single cause of severe and multiple physical disabilities, and rehabilitation that reduces functional deficits is the most effective treatment. The aim of this study was to determine the effect of special education treatment as a supplement to occupational therapy on upper extremities motor skills in adult patients with post stroke hemiplegia. Methods. Standard education tests for motor function evaluation of the upper extremities: O`Connor, Ring and Hand grip test, were applied on a sample of 64 patients who were in the process of rehabilitation in the Clinic for Rehabilitation “Dr. Miroslav Zotović” in Belgrade. After the evaluation, all the participants were included in occupational therapy and divided in two intervention groups per 32 subjects each. The patients from the first experimental group received individually dosed special education treatment which was performed for at least 12 weeks as a supplement together with occupational therapy, while patients from the second experimental group were only in the process of occupational therapy without special education treatment. At the end of the study the same tests were used to re-evaluate the level of motor abilities of the patients in both groups. Results.The patients from the first experimental group with individually dosed special education treatment as a supplement showed significantly better scores after applying the treatment in all tested variables – explosive, static and dynamic muscular strength grip fist, as well as oculomotor skills at the level of the elbow and shoulder for both healthy and paretic hand. Conclusion. On the basis of the obtained results, it can be concluded that special education treatment added to occupational therapy lead to better performing of upper extremities motor skills and that it can be a good supplement to conventional occupational therapy methods and techniques.